High dose-rate brachytherapy as a treatment option in primary tracheal tumors - Carvalho, Heloisa de Andrade; Figueiredo, Viviane; Pedreira Jr., Wilson Leite; Aisen, Salim (Clinics, 2005)
PURPOSE: To present experience with high dose-rate endobronchial brachytherapy in the treatment of primary tracheal tumors. PATIENTS AND METHODS: Four patients with nonresected primary tracheal tumors are presented: 2 cases of squamous cell carcinoma of the trachea, 1 of recurrent adenoid cystic carcinoma, and 1 with recurrent plasmacytoma. All received brachytherapy, alone or as a boost for primary irradiation, in 3 or 4 fractions of 7.5 Gy, calculated at a depth of 1 cm. Follow-up was considered to start from the end of brachytherapy. RESULTS: Local control was achieved in all cases at the time of first bronchoscopic evaluation. Two patients with squamous cell carcinoma died at 6th and 33rd months after brachytherapy, respectively. The first had no evidence of disease, and the latter had local recurrence. The other 2 patients were alive after 64 and 110 months of follow-up, respectively, both with no evidence of disease. Tracheal stenosis developed in these 2 cases, 22 and 69 months after brachytherapy. Tracheal stent placement was needed only for the patient with an adenoid cystic carcinoma. CONCLUSIONS: Endobronchial high dose-rate brachytherapy may be used for tracheal tumors, even as a boost for external beam irradiation, or in recurrences. Local control in 3 out of 4 patients indicates that individual cases may benefit from the treatment. Long-term survival may also be expected, mainly for tumors with adenoid cystic histology.